Laboratory School Protocol Mini-Review: Use of Direct Observational and Objective Measures to Assess ADHD Treatment Response Across the Lifespan - Wigal, Sharon B. (Frontiers in Psychology, 2019)
The time of onset and the duration of treatment effect are important considerations in the choice of the medication to be prescribed in treating children, adolescents and adults with ADHD. Early onset of effect may facilitate preparation for school, improved behavior during the trip to school, and attention during morning classes. Sustained treatment effect through afternoon and evening hours can be important because impairments associated with ADHD are not limited to the naturalistic classroom. Laboratory school protocols (LSPs) provide a simulated, rigorously controlled classroom setting environment and have proven valuable for providing pharmacokinetic and pharmacodynamic information about medications and other treatments used in managing ADHD in school-aged children and across the lifespan. Methods: This paper is an invited mini-review of LSPs of stimulant medication, which includes data from multiple, randomized, double-blind, placebo-controlled medication trials of various treatments for ADHD. Assessment endpoints included the Permanent Product Measure of Performance (PERMP), Swanson, Kotkin, Agler, M-Flynn and Pelham (SKAMP) Rating Scale in the preschool assessment laboratory (PAL), child/adolescent and adult workplace environment (AWE) studies. These measures allow the study of improvement in attention and behavior in individuals with ADHD. Results: Analog classroom settings (LSP or AWE) have been used to assess immediate and modified-release stimulant formulations of medications to treat ADHD in multiple age groups. Results based on both subjective (e.g., SKAMP ratings) and objective (e.g., PERMP) measures are used as clinical outcomes in testing drugs currently in development for ADHD. Conclusion: The LSP and its extension to PAL and AWE settings continue to be used to assess the time-course of effect of ADHD medications because they provide valuable information in their respective structured, controlled environments.